2017
DOI: 10.1016/j.kjms.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Placental apoptosis in recurrent miscarriage

Abstract: Apoptosis is an interactive and dynamic biological process involved in all phases of embryogenesis. We aimed to study the effect of placental apoptosis on recurrent miscarriage (RM). Placental tissue samples were collected from 40 women with RM (study group) and 30 women with sporadic spontaneous abortion (control group). Samples were prepared and stained immunohistochemically with markers for both the apoptotic protein (p53) and anti-apoptotic Bcl-2 antibodies. Our results showed that expression of the apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Perturbed apoptosis regulation is a major causative factor for cancer pathogenesis, including HCC. 7 9 In 1972, Kerret and colleagues 10 defined apoptosis as a form of programmed cell death that depends on adenosine triphosphate and is distinct from necrotic cell death. 8 , 9 Many studies have implicated the role of apoptosis in the pathogeneses of multiple diseases in humans and animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perturbed apoptosis regulation is a major causative factor for cancer pathogenesis, including HCC. 7 9 In 1972, Kerret and colleagues 10 defined apoptosis as a form of programmed cell death that depends on adenosine triphosphate and is distinct from necrotic cell death. 8 , 9 Many studies have implicated the role of apoptosis in the pathogeneses of multiple diseases in humans and animals.…”
mentioning
confidence: 99%
“… 7 9 In 1972, Kerret and colleagues 10 defined apoptosis as a form of programmed cell death that depends on adenosine triphosphate and is distinct from necrotic cell death. 8 , 9 Many studies have implicated the role of apoptosis in the pathogeneses of multiple diseases in humans and animals. 11 15 In development of anticancer drugs, some of the main approaches used are to develop drugs that inhibit excessive growth of tumor cells or promote apoptosis in tumor cells.…”
mentioning
confidence: 99%
“…Several studies have shown that antiapoptotic Bcl-2 levels are lower in the placenta of patients with habitual abortions than in the normal population. 12,29,30 Furthermore, it has been indicated that Bcl-2 expression, which is low in the early weeks of normal pregnancy, increases during late weeks of pregnancy. This increase may provide continuity for the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…11 Apoptosis is seen more frequently in the placenta of patients with habitual abortion than in that of patients with spontaneous abortion. 12 In addition, it has been shown that perivillous fibrin deposition, chronic villitis, chronic histiocytic intervillositis, and plasma cell deciduitis are higher in chromosomally normal habitual abortions than in spontaneous abortions. 13,14,15 Previous studies have also shown that placental invasion disorder is high, rather than thrombosis, in patients with habitual abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis and cell death is associated with SA. Placentas from women with recurrent SA have increased levels of apoptosis compared to women with normal pregnancies (Atia 2017). Exposures to toxic chemicals such as polycyclic aromatic hydrocarbons induce apoptotic pathways and lead to embryonic loss in animal models, a proposed mechanism explaining higher miscarriage rates in women who smoke (Detmar et al 2006).…”
Section: Discussionmentioning
confidence: 99%